PENGARUH KODE ETIK PROFESI AKUNTAN PUBLIK TERHADAP KUALITAS AUDIT PADA KAP DI SURABAYA - Kristofora Tamara; Senny Harindahyani (Perpustakaan Universitas Surabaya, 2018)
Abstract–This study aims to examine the significance of the influence of Code of Ethics of Public Accountant Professionconsisting of principles of integrity, principles of objectivity, principles of competence and the attitude of precision and professional prudence, principle of confidentiality and principle of professional behavior to audit quality. This study was conducted by SPSS 18.Make theindependent auditorwho areworking at Public Accounting Firmlocated in Surabaya which has the last position as a junior auditor, senior auditor and supervisoras a research object. Usingprimary datain the form ofquestionnairesdata that distributed to 80 auditors as respondentsin 2016.The results of this study indicate that the principles of competence and the attitude of precision and professional prudencehave the most significant effect on audit quality with 5% significance. The principle of objectivity and the principle of confidentiality have a significant effect on audit quality with 10% significance. While the principle of integrity and the principle of professional behavior has no effect on audit quality.